Optimization of surface roughness in end milling of titanium alloy TI-6AL-4V under the influence of magnetic field from permanents magnets - Sulaiman, Syidatul Akma; Amin, A. K. M. Nurul; Arif, Muammer Din (Trans Tech Publications, Switzerland, 2012)
This paper presents the effect of cutting parameters on surface roughness in end milling of Titanium alloy Ti-6Al-4V under the influence of magnetic field from permanent magnets. Response Surface Methodology (RSM) with a small central composite design was used in developing the relationship between cutting speed, feed, and depth of cut, with surface roughness. In this experiment, three factors and five levels of central composite with 0.16817 alpha value was used as an approach to predict the surface roughness, in end milling of titanium alloy, with reasonable accuracy. The Design-Expert 6.0 software was applied to develop the surface roughness equation for the predictive model. The adequacy of the surface roughness model was validated to 95% by using ANOVA analysis. Finally, desirability function approach was used to determine the optimum possible surface roughness given the capabilities of the end machine.